Direito em Lukács: gênese e particularidades do complexo jurídico - Lima, Hanna Rafaelli de Brito (2019)
This dissertation has as object the analysis of the legal complex through the maturity work of the Hungarian philosopher György Lukács, Ontology of social being. The particularities of the legal complex are problematized. It is explored the degrees of the being, the work as a founder of the social being, the complexes of social reproduction, the duty and the value, in order to enable the presentation of the right as a partial complex of the complex of complexes that is the social totality. The debate about the function of the legal complex has been gaining strength in the philosophy of right, in the meantime, Lukacs' theoretical contributions produce a wide range of questions and concerns about the specificities of law. From the method of historicaldialectical materialism, the main line which orients this investigation is based, above all, on the analysis of the legal complex in a historical-social way, since the origin of the society of classes coming from the act of work itself until the origin of the law simultaneously to the State, as a particular public force, which primary function consists in the guarantee of the reproduction of the society of classes. The contradictions present in the development of the right are demonstrated as a practical reflection of reality and the possibilities and limits of betting on the legal complex as the guarantor of the overcoming of the inhumanities present in the current sociability. From this, the relations of right with other social complexes are presented, above all the politics, the moral and the ethics, aligning itself theoretically to Lukács by refuting the idealistic conceptions about the right and those derived from vulgar materialism, typical of the 20th century, which conceive the law as merely a mechanical reflection of the economy. The main theoretical landmark is based on the writings of Lukács' maturity, but are also references texts by Marx, Engels, Mészáros, Lessa, Sartori and Andrade, who verse, even if punctually, about the right. Thus, the final disposition of this analysis is to collaborate to the field of research of the law that breaks with its traditional approaches, which conceive, superficially, the law as a self-founded sphere, autonomous, closed in itself, without which there is no possibility of even existing society.